POLA MODERN ORGANISASI PENGEMBANGAN KURIKULUM - Sulaiman Sulaiman (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2013)
Curriculum is one of the important elements in education. Thereof, ideally, any educational institution develops curricula based on the need to follow the principle in relevance to the circumstances and needs of the community. To meet the needs, there are three modern patterns in organizing the curriculum; (Separated Subject Curriculum, Correlated Curriculum, and Integrated Curriculum) become a minimal patron for the educational stakeholder in managing the curriculum. However, there are some aspects which must be considered as the strength and the weaknesses. Besides, it is in line with the pattern applied to ensure that the curriculum is also accompanied by competent teachers in applying the curriculum. As it is seen from the patter’s perspective are still be found some weakness such as Correlated Curriculum, Integrated Curriculum. This model requires that a eacher is able to connect and combine and integrate among one subject with other subjects.